Oregano essential oil supplementation improves productive performance, oxidative stability, and lipid parameters in turkeys (Scientia Agropecuaria, 2020)
The present study evaluated the effect of supplementation with oregano essential oil (OEO) on the productive parameters, oxidative stability, and lipid parameters of turkey meat. Eighty 1-d-old male turkeys were randomly distributed into four treatment groups and fed the following diets for 105 d: control diet without any supplementation or supplementation with 300 mg/kg lincomycin and spectinomycin, 100 mg/kg OEO, or 200 mg/kg OEO. Supplementation with 200 mg/kg OEO obtained the best body weight, average daily gain, feed conversion, and the lowest feed intake with respect to the other diets (p < 0.001), while 100 mg/kg OEO had the best oxidative stability (p < 0.001). Though OEO had no hypocholesterolemic effect, 200 mg/kg OEO produced the lowest concentration of triglycerides in the blood (p < 0.05). In conclusion, OEO supplementation improves productive parameters and increases oxidative stability in turkeys. Therefore, OEO has the potential to act as a growth promoter replacing antibiotics.
Keywords: Oregano essential oil; productive parameters; oxidative stability; lipidic profile; turkey.